Mood recognition as customer’s feedback using fuzzy inference system / Siti 'Aisyah Sa'dan ... [et al.] - Sa'dan, Siti 'Aisyah; Yusof, Noor Hazira; Mohd Bahrin, Ummu Fatihah; Hamzah, Siti Salbiah (Universiti Teknologi MARA, Perak, 2018)
Within the last several years, human mood recognition has been actively explored in the computer vision research. Human mood recognition is widely applied in education, psychology and customer service management. This study has been prepared for the customer service management. Nowadays, customer service is usually conducted through a manual survey to measure the customer’s satisfaction. Manual customer’s satisfaction survey is subjective and the customer’s response may be less accurate. The objective of this study is to develop a mood recognition prototype as customer’s satisfaction feedback using fuzzy inference system and to measure its effectiveness. This study explores the recognition of domain-specific mood using a fuzzy inference system to detect three categories of mood; negative and positive and neutral with the accuracy of 78% matched based on the mouth measurement and computation. The future study focus on adding more feature points and improve rules and combine other classifiers to the fuzzy inference system for better performance.